THE EFFECT OF WORKING CAPITAL, RETURN ON ASSETS AND COMPANY SIZES ON THE CREDIT AMOUNT OF SMALL AND MEDIUM MICRO BUSINESSES IN NATIONAL BANKS IN INDONESIA PRE COVID-19 - Sunaryo, Deni (Dinasti International Journal of Economics, Finance & Accounting, 2020)
The research of "Effect of Working Capital, Return on Assets and Company Size on the Amount of Micro and Small Medium Enterprises Loans at National Banks in Indonesia in Pra COVID-19" was conducted using Multiple Linear Regression analysis tools using the help of SPSS 25 data processing applications. This research is the influence of Working Capital variable on the distribution of MSME loans with t arithmetic> t table (4.992> 2.048) with a significance value of 0.000 <0.05. The Return on Assets (ROA) variable does not affect the distribution of MSME loans to national banks in Indonesia in 2014-2018 with t count <t table (0.025 <2.048) with a significance value of 0.980> 0.05. The company size variable has a significant effect with the value of t count> t table (3.026> 2.048) with a significance value of 0.006 <0.05. Based on a simultaneous study of working capital, Return on Assets (ROA), and company size influence the distribution of MSME loans to national banks in Indonesia in 2014-2018 with a F table of 2.98 and a significance level of 0.05. Then F count> F table (12.041> 2.98) and sig. <0.05 (0,000 <0.05).